Determination of human and veterinary antibiotics in indirect potable reuse systems - Busetti, Francesco; Heitz, Anna (Taylor & Francis, 2011)
This paper reports the optimization and validation of an analytical method for the determination of the residual concentration of the prescription antibiotics metronidazole, trimethoprim, sulfamethoxazole, azithromycin, clindamicyn, clarithromycin, erythromycin-H2O, roxithromycin and tylosin in wastewater and advanced treated wastewater. The method applied was used in a study of removal efficiency of these compounds at a full scale operational water reclamation plant using microfiltration-reverse osmosis (MF-RO) (Kwinana, Western Australia). The analytical procedure involves off-line solid-phase extraction (SPE) followed by liquid chromatography - tandem mass spectrometry (LC-MS/MS) operated in multiple reaction monitoring mode. Method validation included determination of linearity, accuracy, precision, method limits of quantitation (MLQs), reproducibility and matrix effect. SPE recoveries were generally higher than 89% for both pre- and post- RO water, except for erythromycin which yielded approximately 50% recovery. The overall precision of the method was better than 16% RSD (relative standard deviation), for all compounds and matrices. MLQ ranged between 23-53 ng/L and 2.5-31 ng/L for pre- and post- RO water, respectively. In-house reproducibility expressed as RSD was generally better than 10%. Inter-laboratory tests revealed a generally good agreement between concentrations of antibiotics reported by all participants. Results demonstrate that MF/RO treatment is capable of removing antibiotics present at relevant environmental concentration in secondary effluent (from the low to-mid ng/L range) to below MLQs (2.5-31 ng/L), and more importantly, three to six orders of magnitude below the health guideline values developed for this project. Estimated RO rejections ranged between > 91 and 99%.